Assessing the Fiscal Sustainability of Government Finances in European Countries - Melnykov, Yuriy (Lithuanian Journal of Statistics, 2013)
This paper analyses the fiscal sustainability of government finances in the 27 EU countries and Norway using an empirical, statistical approach and ADF tests for a unit root in the time series of the differences between the GDP growth rate and the long-term interest rate, and the primary balance.